Peningkatan Kemampuan Membaca Pemahaman Siswa Kelas IV SDN 100114 Aek Nabara Tobotan Melalui Penggunaan Media Visual - Darwan Situmorang (Institute of Information Technology and Social Science (IITSS), 2020)
The purpose of this study is to improve the reading ability of students in Class IV SDN 100114 Aek Nabara Tobotan through the use of visual media. The research method used is the classroom action research (CAR) method. The subjects of this study were 31 students in Class IV SDN 100114 Aek Nabara Tobotan. To obtain research data, the instruments used were observation sheets and test sheets. In analyzing data, qualitative and quantitative data analysis techniques are used by the authors. The results showed the use of visual media can improve students' reading comprehension of Class IV SDN 100114 Aek Nabara Tobotan. This can be seen from the increase found from cycle I to cycle II. In this case, the authors found the average value of students increased from 67.9 to 74.4 or an increase from 61.2% to 80.6%.